Fly Ash Zeolites Innovations, Applications, and Directions - Jha, Bhagwanjee; Singh, Devendra Narain (Advanced Structured Materials, 2016)
This book presents a thorough review of the state-of-knowledge and recent innovations in the synthesis of pure and improved grades of fly ash zeolites (FAZ). Addressing improvements to conventional methods, it also showcases a novel technique for the synthesis of high cation exchangers from fly ash and detailed characterization techniques for the products obtained. In addition, it examines in detail various areas of specific applications of fly ash zeolites. Over the years, several methods such as hydrothermal, fusion prior to hydrothermal, microwave assisted hydrothermal and molten salt techniques for producing FAZ have been developed. However, one-step and two-step reactions between the fly ash and alkali usually generate alkaline wastes that may cause environmental contamination. In addition, the separation of FAZ from the partially activated fly ash (the impurities) remains a major concern for researchers and industrialists alike. In view of these challenges, this book presents a novel technique for three-step activation (TSA), which focuses on recycling the fly ash-NaOH-water reaction by-products until zeolitic residue is formed. The FAZ (the final residue after third step reactions) synthesized in this manner exhibits exceptionally high cation exchange capacity, specific surface area and pore area. This book offers a comprehensive compendium of reading material on fly ash and its recycled product, the zeolites. Students at both undergraduate and graduate levels, researchers, and practicing engineers will all find this book to be a valuable guide in their respective fields.